Calculation of electric vehicle battery system - Dinh , Tan Ngoc (Journal of Technical Education Science, 2021)
Designing a vehicle is a complex multi-stage process and involves many factors which required carefully in calculation such as: the vehicle’s dynamic, active and passive safety systems, connections on the vehicle, arrangement of devices, etc. The same principles when we design an electric vehicle. In this paper, the researcher showed a method to calculate battery system on an electric vehicle from a vehicle that using an internal combustion engine and still ensure the same output power as the original car. The car only uses Li-ion batteries, the car can travel on a single charge is nearly 300 km. The results have calculated the battery system to satisfy the capacity of the original vehicle. Through the calculated results can be applied on real cars.